Kepuasan Sebagai Variabel Mediasi Pada Penerapan Komunikasi Terapeutik Perawat terhadap Minat Berkunjung Ulang - Prasetyo, Ferdhina Annisa; Widaningsih, Widaningsih (Lembaga Penerbitan Universitas Esa Unggul, 2021)
The background of this research was the number of the patient revisit intention at Tiara Hospital in 2017 had not reached 90%, it only ranged from 78.3% to 83.3%, the rate of patient satisfaction at Tiara Hospital had not reached 95% and nurse communication was a major cause of patient dissatisfaction. The study aimed to analyze the influence of the therapeutic communication application in nursing into patient satisfaction and revisit intention at Tiara Hospital. This study was Causal Explanatory Research with 190 respondents as inpatient at Tiara Hospital Tangerang. The samples were taken using proportionate stratified random sampling technique. The variables of this research were the Therapeutic Communication Application in Nursing as an independent variable, Revisit Intention as the dependent variable, Patient Satisfaction as an intervening variable. The instrument of the research study was a questionnaire with a scale of Likert 5 levels. The data were analyzed using Structural Equation Model (SEM). The results showed that the Therapeutic Communication Application in Nursing had a positive effect on patient satisfaction and Revisit Intention simultaneously, Therapeutic Communication Application in Nursing had a positive effect on patient satisfaction, Patient satisfaction had a positive effect on Revisit Intention. The Therapeutic Communication Application in Nursing positively affected Revisit Intention. Patient Satisfaction was an intervening variable of the Therapeutic Communication Application in Nursing into the Revisit Intention. The findings of this study support the theory of Zeithaml and Bitner (2006) that the higher the level of patient satisfaction, the higher the patient's revisit intenton. The implication of this research was that Tiara Hospital management needs to improve the application of therapeutic communication accompanied by monitoring and evaluation and reduce the workload of nurses in order to increase patient satisfaction and revisit intention.Keywords: Therapeutic Communication, Patient Satisfaction, Revisit Intention